A sputtered CdS buffer layer for co-electrodeposited Cu2ZnSnS4 solar cells with 6.6% efficiency1. Issue 51 (28th June 2015) - Tao, Jiahua; Zhang, Kezhi; Zhang, Chuanjun; Chen, Leilei; Cao, Huiyi; Liu, Junfeng; Jiang, Jinchun; Sun, Lin; Yang, Pingxiong; Chu, Junhao
<x xml:space="preserve">Abstract</x> Cu2ZnSnS4 thin films with thicknesses ranging from 0.35 to 1.85 μm and micron-sized grains (0.5–1.5 μm) were synthesized using co-electrodeposited Cu–Zn–Sn–S precursors with different deposition times.